Dari Keunggulan Menuju Kemenangan: Perjalanan Siswa Sekolah Indonesia Jeddah Menuju Kejayaan Olimpiade Sains Nasional - Malindo Anggraini Puspitasari; Muhammad Thohir; Mardiyah Mardiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research examines the management of the Indonesian School of Jeddah (SIJ) in supporting students towards the National Science Olympiad (OSN), with a focus on a student's academic journey. This research highlights student experiences, management strategies implemented by schools, as well as challenges faced during competition preparation. The role of school and family as main supporting factors is also analyzed. Students who have a strong interest in science are actively involved in extracurricular activities, such as science clubs and research projects, and develop time management skills to balance studies and other activities. The school provides a supportive learning environment, with resources and guidance from competent teachers. The family also makes a significant contribution through moral support and instilling a strong work ethic. This research uses a qualitative-descriptive approach with a case study method, which focuses on one research object to reveal the synergistic role between school and family in shaping student achievement. These findings illustrate the importance of collaboration between schools and families in creating student academic achievement.